2019
DOI: 10.1038/s41467-018-08201-x
|View full text |Cite
|
Sign up to set email alerts
|

Selective hematopoietic stem cell ablation using CD117-antibody-drug-conjugates enables safe and effective transplantation with immunity preservation

Abstract: Hematopoietic stem cell transplantation (HSCT) is a curative therapy for blood and immune diseases with potential for many settings beyond current standard-of-care. Broad HSCT application is currently precluded largely due to morbidity and mortality associated with genotoxic irradiation or chemotherapy conditioning. Here we show that a single dose of a CD117-antibody-drug-conjugate (CD117-ADC) to saporin leads to > 99% depletion of host HSCs, enabling rapid and efficient donor hematopoietic cell engraftment. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
130
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(134 citation statements)
references
References 24 publications
(32 reference statements)
3
130
0
1
Order By: Relevance
“…Anti-CD117 ADCs significantly reduce HSPCs in animal models. 42 A major concern targeting CD117 with a potent ADC is its significant expression outside of the hematopoietic system, which raises the possibility of increased toxicity. 43 The even distribution across the major HSPC subtypes would likely make CD300f a more efficient conditioning agent compared with current AML targets being studied, which often have variable HSPC expression.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-CD117 ADCs significantly reduce HSPCs in animal models. 42 A major concern targeting CD117 with a potent ADC is its significant expression outside of the hematopoietic system, which raises the possibility of increased toxicity. 43 The even distribution across the major HSPC subtypes would likely make CD300f a more efficient conditioning agent compared with current AML targets being studied, which often have variable HSPC expression.…”
Section: Discussionmentioning
confidence: 99%
“…By simultaneously targeting the stem cell compartment and malignant cells, the therapeutic goals of HSCT can hypothetically be achieved with toxicities largely confined to the hematopoietic system. Indeed, recent work in murine 17,18,22,23,25,50 , non-human primates 51,52,53 , and early human trials 54 have demonstrated feasibility and limited toxicities of antibody and ADC-based therapies alongside high efficacy in depleting recipient HSCs and/or malignant cells.…”
Section: Discussionmentioning
confidence: 99%
“…With more gene therapy products on the horizon (such as hemophilia), the application of in vivo HSC transduction could extrapolate genetic treatments to a larger patient population. Further improvements of in vivo HSC gene therapy with HDAd vectors on the road to clinical application include more effective mobilization protocols (particularly for some patients, such as SCD patients), complete elimination of innate responses upon intravenous injection, more advanced capsid modifications that circumvent pre-existing anti-Ad immunity, improved selection regimens [240,255]…”
Section: Discussionmentioning
confidence: 99%